On-farm antimicrobial usage in commercial turkey production in the United States, 2013–2021 - Singer, Randall S.; Schrag, Nora F. D.; Ricke, Isabel; Apley, Michael D. (Frontiers in Veterinary Science, 2023)
A key component of antimicrobial stewardship is the ability to collect antimicrobial use data and ultimately use this information to ensure that administrations are necessary and effective. National antimicrobial sales data cannot help in this capacity because the data lack context, for example, details concerning target species and disease indication. The objective of this study was to continue the development of a system for collecting flock-level on-farm antimicrobial use data from the U.S. turkey industry and to have it be representative of national turkey production in the U.S. This study utilized a public-private partnership to enable collection and protection of sensitive flock-level data from an extremely large industry while releasing deidentified and aggregated information regarding the details of antimicrobial use on U.S. turkey farms over time. Participation was voluntary. Data were collected for the period 2013 through 2021 and are reported on a calendar year basis. Using production statistics from USDA:NASS as a denominator, the data supplied by participating companies represented approximately 67.3% of turkey production in the U.S. in 2013, approximately 69.1% in 2017, and approximately 71.4% in 2021. The data that were submitted for 2021 are based on approximately 149,000,192 turkeys slaughtered and 4,929,773,506 pounds liveweight produced. Detailed prescription records representing approximately 60-70% of the birds were available for the 2018-2021 dataset. The estimated percentage of turkey poults placed that received hatchery antimicrobials decreased from 96.9% in 2013 to 40.5% in 2021. The use of in-feed antimicrobials was practically eliminated, with in-feed tetracycline being the only medically important antimicrobial used in 2021. Use of in-feed tetracyclines decreased approximately 80% between 2013 and 2021. Water-soluble antimicrobial use declined over the study period. Between 2013 and 2021, water-soluble penicillin use decreased approximately 41% but water-soluble tetracycline use increased approximately 22%. Key diseases that were treated with water-soluble antimicrobials included bacterial poult enteritis and clostridial dermatitis. Efforts to reduce the incidence of these diseases would reduce the need for antimicrobial therapy, thereby enabling continued decreases in antimicrobial use without sacrificing animal welfare. However, this will require an investment in research to find efficacious and cost-effective mitigation strategies.